1976
DOI: 10.1002/pssb.2220780136
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on magnetic phase transitions in FeRh and FeRhIr alloys

Abstract: The effect of quasi-hydrostatic pressures up to 100 kbar is investigated on the phase transitions of Fel -a h , alloys by resistivity measurements. The pressure dependence of the first order antiferromagnetic (AF) to ferromagnetic (FM) phase transformation temperature dTk/dp = 4.4 to 6 K/kbar. The pressure dependence of the second order FM to paramagnetic (PM) transition, i.e. that of the Curie-point is dTc/dp = -0.7 K/kbar. At about 60 kbar the thermal hysteresis diminishes, and above the range of the co-exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Excitation of the phase transition occurs when energy is added to the system allowing one to use a wide range of stimuli to induce the metamagnetic phase transition, such as, electric field [11], temperature [1], applied magnetic fields [12,13], pressure [14], and spin-polarized currents [15] making it a tempting candidate for future magnetic-based technological devices.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of the phase transition occurs when energy is added to the system allowing one to use a wide range of stimuli to induce the metamagnetic phase transition, such as, electric field [11], temperature [1], applied magnetic fields [12,13], pressure [14], and spin-polarized currents [15] making it a tempting candidate for future magnetic-based technological devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Numerous studies have shown that variations in the applied external magnetic field as well as strain can modify the magnetostructural phase transition character and transition temperature (henceforth denoted T t ) in both bulk and thin film forms of FeRh. [5][6][7][8] In particular, an applied magnetic field has been demonstrated to linearly decrease the transition temperature at a rate of À8 K/T in both bulk and thin film forms of FeRh. 5,9 Thin film forms of FeRh are particularly interesting due to their heightened sensitivity to strain that may contribute to unique properties such as the observed persistence of retained ferromagnetism below the bulk phase transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The features of the transition such as the critical temperature, the width of the thermal hysteresis, and the abruptness of the transition are extremely sensitive to the chemical composition of the alloy, preparation technique of the samples, and their thermal and mechanical treatment [6,10,14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Thus, the critical temperature of the transition may vary from 143 K up to 408 K when changing the Rh concentration within 47-63 at.% [30,33,34], and from 150 K to 585 K by 3d-, 4d-, and 5d-metal impurities [24,26,30,[34][35][36][37][38][39][40][41]. For example, the critical temperature of the transition in the (Fe 1−x Ni x ) 49 Rh 51 alloys decreases from 320 K for x = 0 to 150 K for x = 0.035 [24].…”
Section: Introductionmentioning
confidence: 99%